Integrasi Low Carbon Education Dalam Kurikulum Pendidikan Calon Guru IPA di Indonesia sebagai Upaya Revitalisasi Peran Pendidikan IPA dalam Merespons Tantangan Ekologis di Masa Depan - Muhammad Syahruddin Amin*; Anna Permanasari; Ida Hamidah (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
Global warming and climate change is the main environmental problems globally. The triggers of this problem is the consumptive behavior and wasteful energy in the community which causes the CO2 emission increase continually. To solve those problem, the environmental education should conducted optimally by intimidated the low carbon education. The purposed of this study was to give an overview establishment of the environmental education curriculum and the load amount of the low carbon education at science education study program. This descriptive study uses the literature analysis method with comparative approach. The documents analysis was the syllabus of environmental courses in four science education study program in Indonesia. Quantitatively showed that the environmental education at science education study program was very minimal, it was only 1 to 2 subjects which consist of 2 to 5 credits, or it is around 1,37%-3,42% from the total term that must be learned. Qualitatively showed that most of the materials on the environmental education subject was very general and basic. The low carbon education materials related to current environmental conditions such as the greenhouse gas, CO2 emission, global warming, green energy, climate change, including green technology was thought very minimal. It can be concluded that environmental lectures in science education study program are currently very minimal teaching about the substance of low carbon education, so it must be reproduced and used as a core content of the environmental materials taught.